The kill order - Dashner, James, 1972- (Delacorte Press, 2013)
Mark and Trina are survivors of the solar flares that hit and devastated the Earth, long before WICKED and the Glade were around and Thomas conquered the Maze. Mark and Trina have found a way to survive, but the deadly disease--causing rage and lunacy in its victims--is coming their way from the eastern United States. Worse, it might not be a natural disease at all. Desperate, Mark and Trina know they have to unlock the mystery of the disease if they want to survive.